Detection of Antibacterial Susceptible Salmonella spp. in Cured Beef with Different Shelf-Life Expectancy - Khairunisa, Mutia Asri; Retnaningrum, Endah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Meat is currently one of the food products with the highest demand ever since 1980, where demand has reached 24.8 kg per year per person as of 2020. With high demand comes intensive farming which causes overuse of antimicrobials for both therapeutic and non-therapeutic reasons, allowing more antimicrobial resistant (AMR) strains of bacteria to occur. In the case of meat products, salmonella is considered one of the more commonly occurring bacteria found in raw meat products. However, with meat’s short shelf-life expectancy, the likeliness of consumers suffering from salmonellosis increases. Thus, preservation methods have been implemented to reduce this likeliness, primarily through curing beef. Although curing may reduce the likeliness of excessive microbial growth, AMR salmonella has been detected in cured beef samples. The scope of this research determines whether there is Salmonella spp. within the cured beef samples, conduct AMR (azithromycin, ciprofloxacin, and ceftriaxone) analysis of the Salmonella spp. isolated from the cured beef samples and enumeration was conducted. The longer the shelf-life expectancy of cured beef samples, the lower the overall CFU/mL per sample was (control: 17,800,000 CFU/mL, >1 year: 0 CFU/mL). It was also discovered that Salmonella spp. has potential resistance towards ciprofloxacin (33.33% intermediate) and susceptibility towards azithromycin and ceftriaxone (100.00% sensitive). This research implies the agricultural industry and safety for consumers of cured beef products with different shelf-life expectancies.